A Monthly Index of Commodity Prices, 1890-1900 - Bacon, Dorothy C. (The Review of Economics and Statistics, 1926)
THE necessity for monthly data for an adequate study of the business conditions of any period is generally recognized. Up to the present, however, no general monthly index of wholesale prices for the decade I890-99 has been available. It is the purpose of this article to present a general index of prices which was developed in connection with a study of price maladjustment for this decade. The new monthly index for I890-99 together with quarterly indexes for I859-89 and the monthly index of the United States Bureau of Labor Statistics for I900-26 are given in Chart i.